(?,?) Statistical Convergence of Order 7 for Double Sequences of Functions - Cinar, Muhammed; Seker, Dilan; Et, Mikail (E D P Sciences, 2018)
In this present work, we investigate the concepts of Delta(r) - statistical convergence of order (gamma) over tilde for double sequences of real valued functions. Also some definitions we given for Delta(r) - statistical Cauchy sequence for double sequences of real valued functions and some relations between S-(lambda,S-mu)((gamma) over tilde)(Delta(r), f)(Ar, f) statistical convergence and strong left perpendicular (gamma) over tilde, lambda, mu right perpendicular(q) (Delta(r) f)-summability are given.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS